2007
DOI: 10.1620/tjem.212.341
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Suicide-Inactivation of Tyrosinase: A Substrate Structure Investigation

Abstract: . The Mechanism of Suicide-Inactivation of Tyrosinase: A Substrate Structure Investigation. Tohoku J. Exp. Med., 2007, 212 (4), [341][342][343][344][345][346][347][348] Tyrosinase is a copper-containing mono-oxygenase, widely distributed in nature, able to catalyze the oxidation of both phenols and catechols to the corresponding ortho-quinones. Tyrosinase is characterised by a hitherto unexplained irreversible inactivation which occurs during the oxidation of catechols. Although the corresponding catechols are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
93
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(106 citation statements)
references
References 28 publications
12
93
1
Order By: Relevance
“…In addition to substrate activation, PPO from various sources, including lettuce has been shown to suffer from suicide inhibition, i.e. irreversible inhibition by a substrate analogue that occurs during the natural metabolic process (Chazarra et al 1999;Land et al 2007). In tyrosinase from Agaricus bisporus, these have been identified as catechols (o-diphenols) of various specific structures (Land et al 2007).…”
Section: Biochemistry Of Oxidative Discolourationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to substrate activation, PPO from various sources, including lettuce has been shown to suffer from suicide inhibition, i.e. irreversible inhibition by a substrate analogue that occurs during the natural metabolic process (Chazarra et al 1999;Land et al 2007). In tyrosinase from Agaricus bisporus, these have been identified as catechols (o-diphenols) of various specific structures (Land et al 2007).…”
Section: Biochemistry Of Oxidative Discolourationmentioning
confidence: 99%
“…irreversible inhibition by a substrate analogue that occurs during the natural metabolic process (Chazarra et al 1999;Land et al 2007). In tyrosinase from Agaricus bisporus, these have been identified as catechols (o-diphenols) of various specific structures (Land et al 2007). Oxidation of diquinones produced at cut surfaces could theoretically lead to the production of small amounts of inhibitory catechols.…”
Section: Biochemistry Of Oxidative Discolourationmentioning
confidence: 99%
“…In these experiments the catechol substrate (ca 0.4 mM) was added to the enzyme solution (300 units mL . 18 Thus, the rates of quinomethane formation are too slow to account for the inactivation. In a final experiment to support the conclusion that para-quinomethanes are not responsible for inactivation of tyrosinase we have shown that 4-methoxycatechol causes inactivation (k i 3.1 x 10 -2 s -1 ) even though it cannot form a quinomethane.…”
Section: Methodsmentioning
confidence: 99%
“…We have proposed that in addition to the normal catecholase oxidation that occurs via the complex 4 (Scheme 2A), a fraction of the catechol substrate presents itself as a cresolase substrate (Scheme 2B). 18 The alternative enzyme substrate complex 5 can undergo deprotonation and reductive elimination leading irreversibly to Cu(0) and inactive tyrosinase. …”
Section: Introductionmentioning
confidence: 99%
“…Recently we proposed a mechanism that accounts for the copper loss during inactivation. 18 Briefly stated, this mechanism postulates that oxy-tyrosinase 1 sometimes binds catechol substrates in the oxygenase mode, i.e. as if they were phenols.…”
Section: Suicide Inactivation By Catechol Substratesmentioning
confidence: 99%